An integrated bioinformatics approach for identification of key modulators and biomarkers involved in atrial fibrillation. - Thahiem, Summan; Ishtiaq, Ayesha; Iftekhar, Faisal; Jan, Muhammad Ishtiaq; Murtaza, Iram (Journal of Cardiovascular & Thoracic Research, 2025)
Introduction: Atrial fibrillation (AFib) is a sustained form of cardiac arrhythmia that occurs due to sympathetic overdrive, neurohumoral and electrophysiological changes. Sympatho-renal modulatory approach via miRNA-based therapeutics is likely to be an important treatment option for AFib. The study was aimed to unravel the common miRNAs as therapeutic targets involved in sympatho- renovascular axis to combat AFib. Methods: We employed the bioinformatics approach to discover differentially expressed genes (DEGs) from microarray gene expression datasets GSE41177 and GSE79768 of AFib patients. Concomitantly, genes associated with sympathetic cardio-renal axis, from Genetic Testing Registry (GTR) of National Center for Biotechnology Information (NCBI) were also analyzed. Overlapping miRNAs that target the maximum number of genes across all three pathological conditions perpetuating AFib were shortlisted. To confirm the reliability of the identified miRNAs, differential expression analysis was performed on miRNA expression profiles GSE190898, GSE68475, GSE70887 and GSE28954 derived from AFib patient samples. Results: ShinyGO analysis revealed enrichment in beta-adrenergic signaling, calcium signaling, as well as G protein-coupled receptor (GPCR) signaling involved in post synaptic membrane potential. The intersection of top 10 modules in miRNA-mRNA network revealed hub miRNAs having highest node degree, maximum neighborhood component (MNC), and maximal clique centrality (MCC) scores. Differential expression analysis revealed hub miRNAs identified through integrated approach were found to be significantly dysregulated in AFib patients. Conclusion: This integrated approach identified 6 hub miRNAs, 4 reported (miR-101-3p, miR-23-3p, miR-27-3p, miR-25-3p) and 2 novel (miR-32-5p, miR-92-3p) miRNAs that might act as putative biomarkers for AFib.